Eighth Five Year Plan 1992-97 Volume I - Planning Commission (Planning Commission, 1992)
We are launching the Eighth Five Year Plan in the backdrop of widespread changed which have altered the international social and economic order. Centralised economies are opening up to free market forces and competition. We are also witnessing an eventful release of people 's power for creative freedom and active involvement in restructuring the economic order for human development. This tidal wave of change has not left India untouched. In these trying and turbulent times, we have to respond and adjust to the changes quickly and creatively. The challenges before us are many. Fiscal problems restrict the ability of the Government to provide needed resources to maintain the impetus of growth. At the same time, we have to ensure that the stimulus for sustaining the long-term growth of the economy is strengthened in the immediate future. The process of economic reforms and structural adjustments has to be carried forward without sacrificing the imperatives of development. This calls for a delicate balancing of options in the formulation of the Plan. 3. We have to start rolling back the Public Sector investment from those sectors of the economy where the private sector can move in and step up our investment in the social sector. At the same time, we have to ensure that the infrastructure needed for economic development continues to grow in this transitional period.
Objectives, Perspective, Macro-Dimensions, Policy Framework and Resources